Advances in Service-Oriented and Cloud Computing Workshops of ESOCC 2014, Manchester, UK, September 2-4, 2014, Revised Selected Papers - Ortiz, Guadalupe; Tran, Cuong (Communications in Computer and Information Science, 2015)
This volume contains the technical papers presented in the four high-quality workshops associated with the European Conference on Service-Oriented and Cloud Computing, ESOCC 2014, held in Manchester, UK, in September 2014: 4th International Workshop on Adaptive Services for the Future Internet, WAS4FI 2014, 2nd International Workshop on Cloud for IoT, CLIoT 2014, 2nd International Workshop on Cloud Service Brokerage, CSB 2014, and Seamless Adaptive Multi-cloud Management of Service-based Applications, SeaCloudS Workshop. The 19 revised full papers and 3 short papers were carefully reviewed and selected from 39 submissions. They focus on specific topics in service-oriented and cloud computing domains as cloud computing, service buses, Web services, service-oriented architectures, event-driven architectures, enterprise architectures, business process management, software selection and adaptation.